IJCM_179A: Prevalence of Overweight and Obesity among M.B.B.S students. - Nigam Manas; Verma Prashant; Gupta Preeti (Wolters Kluwer Medknow Publications, 2024)
Background: Overweight and obesity are defined as abnormal or excessive fat accumulation that may impair health. Prevalence of overweight and obesity is rising in India. Medical students are vulnerable to overweight and obesity because of the sedentary lifestyle which is frequently adopted due to massive work burden, erratic food timings and exposure to stressful situations. Obesity is a well known risk factor for diabetes, hypertension, fatty liver disease, gall stones and osteoarthritis. Hence, this study is taken up to assess prevalence of overweight and obesity among M.B.B.S students. Objective: To assess prevalence of overweight and obesity and associated factors among M.B.B.S students in N.S.C.B Medical College, Jabalpur, Madhya Pradesh. Methodology: A descriptive cross - sectional study is conducted among medical students of N.S.C.B Medical College, Jabalpur, Madhya Pradesh. Socio demographic details are recorded using structured proforma. Anthropometric and clinical parameters are measured using standard techniques. The data will be analyzed using SPSS software. Statistical analysis will be done by using appropriate statistical test. Results: Out of 310 medical students 61% (189) were males and 39% (121) were females. Prevalence of overweight and obesity according to WHO classification of BMI, was 14.33% and 3.34% respectively and according to Asia Pacific classification, it was 9.7 % and 17.66 % respectively. Significant association was found between overweight/obesity and eating junk food and carbonated drinks (p<0.05) and habit of munching between meals (p<0.05). Conclusion: Prevalence of overweight and obesity was 14.33% and 3.34% respectively among medical students of NSCB Medical College, Jabalpur, MP.